Influence of Financial Performance and Fair Price of Share on Investment Decisions with Good Corporate Governance as Moderating Variables in Companies in The Indonesia Stock Exchange - Masno Marjohan (MIX: JURNAL ILMIAH MANAJEMEN, 2023)
Objectives: The goal of this research is to research and determine the influence of financial performance and fair share price on investment decisions with competent management for a Real Estate and Construction Property firm listed on the Indonesia Stock Exchange from 2016 to 2020.Methodology: This study adopts a descriptive methodology of quantitative, the collection of financial statements of 51 companies that have been registered with the IDX. The measurement model and hypothesis testing are carried out using Views 9 software.Finding: The results showed that Return on Equity, Current Ratio, and Debt Equity Ratio had no effect, but Total Asset Turnover and Price Book Ratio influenced investment decisions.Conclusion: Investment decisions are not influenced by financial performance (ROE, CR, and DER), but they are influenced by other financial performance (TATO, and PBV). While good corporate governance does not moderate (weaken) the impact of a company's financial performance on investment decisions, it does moderate (strengthen) the impact of fair price shares (PBVs).